In‐Situ Electrochemically Activated Surface Vanadium Valence in V2C MXene to Achieve High Capacity and Superior Rate Performance for Zn‐Ion Batteries - Liu, Ying; Jiang, Yue; Hu, Zhe; Peng, Jian; Lai, Weihong; Wu, Dianlun; Zuo, Shouwei; Zhang, Jing; Chen, Bin; Dai, Ziwen; Yang, Yingguo; Huang, Yang; et al. (Advanced functional materials, 2021)
Vanadium‐based materials are fascinating potential cathodes for high energy density Zn‐ion batteries (ZIBs), due to their high capacity arising from multi‐electron redox chemistry. Most vanadium‐based materials suffer from poor rate capability, however, owing to their low conductivity and large dimension. Here, we propose the application of V2C MXene (V2CTx), a conductive 2D nanomaterial, for achieving high energy density ZIBs with superior rate capability. Through an initial charging activation, the valence of surface vanadium in V2CTx cathode is raised significantly from V2+/V3+ to V4+/V5+, forming a nanoscale vanadium oxide (VOx) coating that effectively undergoes multi‐electron reactions, whereas the inner V‐C‐V 2D multi‐layers of V2CTx are intentionally preserved, providing abundant nanochannels with intrinsic high conductivity. Owing to the synergistic effects between the outer high‐valence VOx and inner conductive V‐C‐V, the activated V2CTx presents an ultrahigh rate performance, reaching 358 mAh g−1 at 30 A g−1, together with remarkable energy and power density (318 Wh kg−1/22.5 kW kg−1). The structural advantages of activated V2CTx are maintained after 2000 cycles, offering excellent stability with nearly 100% Coulombic efficiency. This work provides key insights into the design of high‐performance cathode materials for advanced ZIBs. An effective strategy to unleash the potential of V2C MXene for fast Zn‐ion storage is developed via regulating the valence of surface vanadium while preserving the inner 2D conductive V‐C‐V layers, which forms a VOx/V2CTx heterostructure. This heterostructure not only offers abundant active sites for Zn2+ storage, but also provides ordered nanochannels for rapid electron/ion transfer.